Role of Bleomycin in Treatment of Cystic Hygroma - Sunil Kumar Saxena; Shalini Hajela (International Journal of Medical Research and Review, 2014)
Introduction: Cystic hygroma is a congenital multiloculated lymphatic lesion which most commonly occurs in cervicofacial region (posterior triangle of neck) and axilla. It is a benign cystic variety and the commonest form of lymphangioma. It contains watery fluid consistent with lymph. Bleomycin is a chemotherapeutic agent which acts by causing breaks in DNA. We used bleomycin, an intralesional sclerosing agent as an alternative to surgical excision.Methods: After written informed consent of the guardians of the patients, all the patients were given intralesional bleomycin injection at the dose of 0.2 mg/kg body weight. Under all aseptic precautions, the lymphatic fluid was aspirated completely and injection bleomycin was given from same site. This injection was repeated at an interval of 4 weeks. Post operatively compression dressing was done for 24 hrs.Results: Complete resolution of cystic hygroma was seen in 21(42%) patients while partial response in 18 (36%). No response, which is accumulation of lymphatic fluid in the cyst after repeated injection of bleomycin for 4 times, was noted in 11 (22%) patients. Complications such as local irritation, redness at the injection site or fever occurred in 7 patients which were controlled with antibiotic and antiallergic therapy.Conclusion: Intralesional bleomycin can be used as first line of management in patients with large cystic hygroma, since it avoids invasive surgery and reduces risk of damage to vital organs. It is a safe, simple and effective method and can be done on day care basis.